ISOLATION OF MOUSE NEUTROPHILS - Swamydas, Muthulekha (Curr Protoc Immunol, 2015)
Neutrophils represent the first line of defense against bacterial and fungal pathogens. Indeed, patients with inherited and acquired qualitative and quantitative neutrophil defects are at high risk for developing bacterial and fungal infections and suffering adverse outcomes from these infections. Therefore, research aiming at defining the molecular factors that modulate neutrophil effector function under homeostatic conditions and during infection is essential for devising strategies to augment neutrophil function and improve the outcome of infected individuals. This unit describes a reproducible density gradient centrifugation-based protocol that can be applied in any laboratory to harvest large numbers of highly enriched and highly viable neutrophils from the bone marrow of mice both at the steady state and following infection with Candida albicans as described in UNIT 19.6. In another protocol, we also present a method that combines gentle enzymatic tissue digestion with a positive immunomagnetic selection technique or Fluorescence-activated cell sorting (FACS) to harvest highly pure and highly viable preparations of neutrophils directly from mouse tissues such as the kidney, the liver or the spleen. Finally, methods for isolating neutrophils from mouse peritoneal fluid and peripheral blood are included. Mouse neutrophils isolated by these protocols can be used for examining several aspects of cellular function ex vivo including pathogen binding, phagocytosis and killing, neutrophil chemotaxis, oxidative burst, degranulation and cytokine production, and for performing neutrophil adoptive transfer experiments.